Smoking-Cough, Vaccination in Relation with Socio-Economic, Working-Living Conditions among Garment Workers (Global Journal of Medical Research, 2013)
This study attempted to calculate prevalence as well as to identify the patterns of smoking, cough and vaccination (BCG) coverage among garment workers in Dhaka city, Bangladesh. In this study 5829 garment workers from 12 garment factories were interviewed with a pretested questionnaire. The results revealed that 7.3%, 12.3% and 59.6% of garment workers respectively smoked cigarette, had cough and took BCG vaccination. Smoking was significantly associated with age and gender, whereas cough was significantly associated with education (>10 years education) and monthly salary and in case of vaccination, a significant relationship was seen with age, education, monthly salary (4001 BDT), room size (6001-800 and 8001 sq. ft.), status of light and air in the working room, sitting arrangement, number of persons living in a room (5-6 persons), length of living room (9 ft.) and width of living room (5-7 and 8 ft.). In case of BCG vaccination the significant associations appeared with age (25-34 and 35 years), education (6-10 years) and amount of Salary (4001 BDT). TB burden could be reduced significantly by considering the above mentioned factors.
Keywords: smoking-cough; BCG vaccination; garment workers; living-environment